Behaviour of cold formed steel under axial compression force - Tan, Hean Seong (2008)
This master project describes a series of compression test performed on lipped channel columns fabricated from cold formed high tensile steel plates with nominal yield stress of 550 MPa. This test includes Lysaght C-section ranging from C10010 to C20024 with restraint length of 800 mm, 1300 mm & 1500 mm. Each length represents different slenderness ratios, ?1 values (L/ry) ranging from 13.28 to 24.91 and each different section represents different slenderness ratios ?2 values (D/t,B,t & B/D) ranging from 83.3 to 101.3 for D/t, 31.6 to 42.6 for B/t and 0.315 to 0.335 for B/D. The objective of this project was to study the buckling mode of cold formed singly C-section with different restraint lengths and to determine the ultimate compression capacity of the C- section with different section properties. Axial compression tests were performed on the C-section with two pinned ends connection. The pinned end connections base plate consisted of 6 mm thick plate grade G 43A (yield strength 275 N/mmÂ²). The C-section was bolted to the base plate using 4 nos M20 diameter bolt grade 8.8. Gridlines were drawn on the specimen surface measured at 3 cm x 3 cm The cold formed C-sections have high width/thickness ratio that lead to local and distortional buckling affecting mainly member with or without edge stiffeners. The effect of width to thickness ratio increases as the local buckling and distortional buckling capacity decrease. For distortional buckling mode of failure, few parameters play an important role for a cold formed steel to fail under this mode. Among the parameters are flange length, length of lipped and web depth. Other buckling modes such as flexural and flexural-torsional buckling were also observed.